Staying alive : the survival and importance of Atlantic salmon post-spawners - Halttunen, Elina (University of Tromsø, 2011)
The papers of this thesis are not available in Munin: 1. Elina Halttunen, Audun H. Rikardsen, Jan G. Davidsen, Eva B. Thorstad and J. Brian Dempson: 'Survival, migration speed and swimming depth of Atlantic Salmon Kelts during sea entry and fjord migration', Reviews: Methods and Technologies in Fish Biology and Fisheries (2009) Volume 9, Part I, Part 1, 35-49. Available at http://dx.doi.org/10.1007/978-1-4020-9640-2_3 2. Elina Halttunena, Audun H. Rikardsen, Eva B. Thorstad, Tor F. Næsje, Jenny L.A. Jensen and Øystein Aas: 'Impact of catch-and-release practices on behavior and mortality of Atlantic salmon (Salmo salar L.) kelts', Fisheries Research (2010) vol 105, 141–147. Available at http://dx.doi.org/10.1016/j.fishres.2010.03.017 3. Elina Halttunen, Jenny Lovisa Alexandra Jensen, Tor Fredrik Næsje, Jan Grimsrud Davidsen, Eva Bonsak Thorstad, Cedar Marget Chittenden, Sandra Hamel, Raul Primicerio and Audun Håvard Rikardsen: 'State-dependent migratory behaviour of post-spawned Atlantic salmon (Salmo salar)' (unpublished paper). 4. Elina Halttunen, Audun Håvard Rikardsen, Ola Ugedal, Eva Bonsak Thorstad, Jenny Lovisa Alexandra Jensen and Tor Fredrik Næsje: 'The significance of repeat spawning for the production of Atlantic salmon (Salmo salar)' (unpublished paper). Summary Atlantic salmon (Salmo salar L.) repeat-spawners might play an important role in population persistence by increasing both total recruitment and long-term stability of a population. This is because repeat spawners return at larger sizes and with greater fecundity than first time spawners, and the large majority of repeat-spawners are females. Nevertheless, little knowledge exists of this potentially significant population sub-unit. We conducted a four-year field study in the River Alta, Northern Norway, using acoustic and radio telemetry combined with scale sample analysis and mark recapture, with the aim of 1) assessing the survival and migration patterns after spawning, 2) assessing the post and repeat-spawner mortality in the fisheries, ...